Identification of wintertime carbonaceous fine particulate matter (PM2.5) sources in Kaunas, Lithuania using polycyclic aromatic hydrocarbons and stable carbon isotope analysis. (15th September 2020) - Garbarienė, I.; Garbaras, A.; Masalaite, A.; Ceburnis, D.; Krugly, E.; Kauneliene, V.; Remeikis, V.; Martuzevicius, D.
Abstract: The study aimed at demonstrating the application of PAHs and δ 13 C indoor and outdoor measurements towards resolving airborne carbonaceous particle sources in wintertime. Concurrent outdoor and indoor measurements of PM2.5 and size-resolved (PM0.056-2.5 ) particulate matter were conducted at 6 one-family houses in Kaunas, Lithuania during January–March 2013. PM2.5 and size-resolved filter samples were analyzed for total carbon (TC) and stable carbon isotopic composition by elemental analyzer connected to isotope ratio mass spectrometer. Moreover, the indoor-outdoor concentrations of 10 selected polycyclic aromatic hydrocarbons (PAHs) in PM2.5 were quantified. The simultaneous stable carbon isotope ratio and PAHs diagnostic ratio analysis enabled to identify main anthropogenic sources (traffic, biomass burning, and coal combustion) of PM2.5 . Our study indicated that during winter period outdoor PM2.5 in Kaunas were mainly derived from biomass burning (solid fuel stoves) and vehicular emissions. Whereas indoor particulate matter had different stable carbon isotope composition of TC indicating the existence of pollution sources which was likely cooking emissions. The differences of indoor/outdoor stable carbon isotope composition in PM2.5 and size-resolved aerosol particles supported the existence of distinct TC sources and suggested that cooking emissions inside the house could strongly affect δ 13 C values. Graphical abstract: Image 1 Highlights: δ 13 CTC and PAHs in PM2.5 were analyzed in indoor/outdoor environment. The main wintertime outdoor TC sources were biomass burning and local traffic. Indoor δ 13 CTC of PM0.056-2.5 were mostly depleted in 13 C comparing to the outdoor. δ 13 C and PAHs diagnostic ratios were proved to be a suitable tracers of TC sources.